Challenging Students Moral Laziness: Authentic Education Based on Existentialist Philosophy - Herianti, Herianti; Samsuddin, Samsuddin; Rudhi, Rudhi (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Modern educational environments often face students' moral laziness, manifested as ethical passivity, reluctance to make difficult moral decisions, and a tendency to simply imitate norms without internalizing authentic values. Overly normative character education fails to foster a sense of personal responsibility and moral authenticity. Therefore, this study aims to reformulate the concept of authentic education based on the principles of existentialist philosophy (Sartre, Kierkegaard, and Camus) to challenge moral laziness and encourage students to become active and responsible moral agents. The method used is a qualitative philosophical study with interpretive content analysis. Core concepts of existentialism, such as freedom, responsibility, authenticity, and existential anxiety, are transformed into an applicable pedagogical framework. The findings indicate that the resulting Authentic Education emphasizes a pedagogy of awareness, in which students are encouraged to recognize their radical freedom of choice and the consequences of absolute responsibility for those choices. The learning process must create boundary situations (such as real ethical dilemmas) that force students to confront anxiety and choose their own values rather than accept predetermined ones. This article makes a theoretical contribution by offering an existentialist alternative to rule-based moral education, as well as a practical contribution in the form of a basis for designing a curriculum that focuses on developing moral authenticity and personal commitment, preparing students to act ethically in the real world.